PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN KEMAMPUAN SISWA PADA MATERI LIMIT FUNGSI ALJABAR PADA SMA NEGERI 1 KEMBANG TANJONG - Agustami Agustami (Universitas Jabal Ghafur, 2022)
The purpose of this study was to determine the improvement of students' abilities in class XII MIPA-4 material on the limit of algebraic functions in Mathematics by using the Jigsaw type cooperative learning model at SMA Negeri 1 Kembang Tanjong. The benefit of this research is to make it easier for students to learn, especially Mathematics, especially the material on the limit of algebraic functions by using the Jigsaw type of cooperative learning model. The subjects in this classroom action research are students of class XII MIPA-4 SMA Negeri 1 Kembang Tanjong for the academic year 2021/2022, while the object is learning the material for limiting algebraic functions taught with the Jigsaw type cooperative learning model. From the research conducted by examining the students' pre-cycles as measured by written test tools and the results of classroom action research with 2 cycles, it was seen that there was an increase in the results achieved by students in mastering the material on the limits of algebraic functions given. The increase in the average value of 60 in the pre-cycle becomes 69.64 in the first cycle and becomes 82.14 in the second cycle. The percentage of completeness from 32.14% in the pre-cycle to 53.57% in the first cycle and increased in the second cycle to 89.28%.Keywords: Jigsaw Cooperative Learning Model, Student Ability